Genome-Wide Association Mapping and Gene Expression Analyses Reveal Genetic Mechanisms of Disease Resistance Variations in Cynoglossus semilaevis - Zhou, Qian; Su, Zhencheng; Li, Yangzhen; Liu, Yang; Wang, Lei; Lu, Sheng; Wang, Shuanyan; Gan, Tian; Liu, Feng; Zhou, Xun; Wei, Min; Liu, Guangjian; et al. (Frontiers in Genetics, 2019)
The sustainable development of aquaculture has been impeded by infectious diseases worldwide. However, the genomic architecture and the genetic basis underlying the disease resistance remain poorly understood, which severely hampers both the understanding of the evolution of fish disease resistance traits and the prevention of these diseases in the aquaculture community. Cynoglossus semilaevis is a representative and commercially-important flatfish species. Here we combined GWAS and Fst and nucleotide diversity filtration to identify loci important for the disease resistance. Based on 1,076,778 SNPs identified from 650 Gb genome re-sequencing data of 505 individuals, we detected 33 SNPs significantly associated with disease resistance and 79 candidate regions after filtration steps. Both the allele frequencies and genotype frequencies of the associated loci were significantly different between the resistant and susceptible fish, suggesting a role in the genetic basis of disease resistance. The SNP with strongest association with disease resistance was located in Chr 17, at 145 bp upstream of fblx19 gene, and overlapped with the major QTL previously identified. Several genes, such as plekha7, nucb2 and fgfr2, were also identified to potentially play roles in the disease resistance. Furthermore, the expression of some associating genes were likely under epigenetic regulations between the bacterial resistant and susceptible families. These results provide insights into the mechanism that enable variation of disease resistance to bacterial pathogen infection. The identified polymorphisms and genes are valuable targets and molecular resources for disease resistance and other traits, and for advanced breeding practice for superior germplasm in fish aquaculture.